45 Progression of cardiac amyloid fibril infiltration in cardiac amyloidosis using cardiac magnetic resonance. (October 2018) - Connolly, M; Fallon, A; Waterhouse, D; O'Hanlon, R
Abstract : Introduction: The prognosis and treatment of the two main types of cardiac amyloidosis, immunoglobulin light chain (AL) and transthyretin (ATTR) amyloidosis, are substantially influenced by cardiac involvement. Focal myocardial fibrosis is best detected and quantified by cardiovascular magnetic resonance (CMR) and late gadolinium enhancement (LGE) technique. Diffuse subendocardial and transmural LGE is a marker of late cardiac amyloidosis. This report describes the use of CMR to detect early cardiac manifestations in amyloidosis and to evaluate its progression over a five-year period. Methods: Mr GS is a 77 year old gentleman who was diagnosed with cardiac amyloidosis in 2012. He attends follow-up annual review appointments at the National Amyloid Centre in University College London. He has undergone annual CMR at Blackrock clinic Dublin from 2014 until 2017. GS underwent LGE imaging for myocardial scar using a segmented Inversion recovery-technique 10 to 15 min after injection of 0.1 mmol/kg of gadolinium. Myocardial enhancement was assessed visually and interpreted by two cardiac CMR-trained physicians. Results: A short axis of LGE imaging from GS is shown in figure 1 which demonstrates significant, confluent myocardial fibrosis throughout the myocarium. Figure 2 highlights the evolution of amyloidosis from 2014–2017 which shows a gradual increase in LGE uptake throughout the vertical long axis (VLA), horizontal long axis (HLA) and short axis (SA) images. There has been a clear deterioration in appearances with the most striking images of LGE seen in November 2017. The findings correspond with functional deterioration in heart failure symptoms and increasing B-type natriuretic peptide (BNP), peaking at 7, 500 pg/ml. Conclusion: LGE is a sensitive parameter for the early diagnosis of cardiomyopathy in amyloidosis and can be used to show progression of disease.